Pharmaceutical residues in water and sediment of Msunduzi River, KwaZulu-Natal, South Africa - Matongo, Solomon; Birungi, Grace; Moodley, Brenda; Ndungu, Patrick (Chemosphere, 2015)
The little data about pharmaceutical residue contamination in African water bodies motivated our study on the occurrence of pharmaceutical residues in the water and sediment of Msunduzi River in the KwaZulu-Natal province of South Africa; and in the Darvill wastewater treatment plant found in Msunduzi catchment. Samples collected along the River and wastewater treatment plant were extracted and analysed for pharmaceutical residues selected based on statistics of drug usage in South Africa i.e. antipyretics, antibiotics, caffeine, an antiepileptic and an antipsychotic drug were determined using HPLC–MS/MS. In all the matrices investigated, the antipyretic ibuprofen had the highest concentration of up to 117 lg L 1, 84.60 lg L 1 and 659 ng g 1 in wastewater, surface water and sediment respectively. Antibiotics were detected in generally low concentrations of <10 lg L 1 in surface water samples and up to 34.50 lg L 1 in wastewater; moreover they were not completely removed during wastewater treatment. The percentage removal efficiency of the studied group was 6.55–98.00% for antipyretics, 73.33– 98.90% for antibiotics, 48.80% for the anti-epileptic drug and 86.40% for Caffeine. Clozapine exhibited a negative removal. In surface water, Henley dam exhibited a high concentration of the pharmaceutical residues and the highest concentration of metronidazole in sediment (up to 1253.50 ng g 1) detected. Metronidazole was only detected in sediment and bio-solids.
Keywords: Pharmaceutical residues; Surface water; Wastewater treatment plant; Msunduzi River; South Africa